Effectiveness of Monetary Policy and the Utilization of Digital Economy in Maintaining Financial System Stability in Indonesia - Irfan Fauji; Bachtiar Efendi (International Journal of Economics and Management Sciences, 2025)
The digital economy has significantly transformed economic growth by introducing innovations in payment systems and financial services. The modernization of payment instruments through monetary policy has enhanced the ability to control inflation and ensure financial system stability. This study aims to analyze the effectiveness of monetary policy and the utilization of the digital economy in maintaining financial stability in Indonesia. Using time series data from 2010 to 2024 obtained from the World Bank, this research applies the Vector Autoregression (VAR) method to examine both short-term and long-term relationships among variables, including e-money, money supply, inflation, exchange rate, interest rate, and credit card usage. The results show that e-money has a significant reciprocal influence on the money supply, while inflation is also affected by e-money and interest rates. The impulse response function demonstrates that the interactions among these variables tend to converge towards equilibrium over time. Variance decomposition analysis indicates that in the short term, e-money primarily drives financial stability, whereas in the medium and long term, the money supply plays a dominant role. Overall, the findings suggest that monetary policy, supported by digital economic systems, effectively enhances financial system stability in Indonesia. This research contributes to understanding the dual effect of digital payment innovations and provides recommendations for policymakers to strengthen financial inclusion, economic resilience, and macro-financial stability in the digital era.